Mucus from different fish species alleviates carrageenan-induced inflammatory paw edema in rats - Terzi̇, Ertuğrul; Sonmez, A. Y.; Çorum, Orhan; Ozbek, Mehmet; Üney, Kami̇l; Hi̇ti̇t, Mustafa; Arslan, Gökhan (Medknow, 2020)
Objective: To determine the anti-inflammatory effects of mucus obtained from different fish species on the carrageenan-induced acute paw edema in rats. Methods: Forty-two rats were randomly divided into seven groups. Acute paw edema was induced by 0.1 mL of 1% carrageenan, and a single dose of diclofenac and lyophilized mucus (25 mg/kg) of rainbow trout, brook trout, European sea bass, and gilthead sea bream were administered to rats through gastric gavage 1 h before carrageenan treatment. Rat paws were measured before and 1-4 h after carrageenan treatment. The mRNA expressions of cytokines (TNF-α, IL-1β, IL-6, IL-10, and TGF-β), antioxidant markers (catalase and superoxide dismutase), and COX-2 were investigated using quantitative polymerase chain reaction. The histopathological changes were evaluated by hematoxylin and eosin staining. Results: The inhibition percentage of carrageenan-induced paw edema by different fish mucus ranged from 52.46% to 74.86% at 4 h. Histopathological evaluation showed that all fish mucus diminished carrageenan-induced edema and inflammatory cell infiltration. The upregulation of IL-1β mRNA induced by carrageenan was decreased by the mucus of rainbow trout and gilthead sea bream while an increase in the expression of IL-6 mRNA was reduced by the mucus of rainbow trout, brook trout, and gilthead sea bream. In addition, the mRNA expression of superoxide dismutase was higher in the rainbow trout mucus group than the carrageenan group. Conclusions: Mucus obtained from different fish species may have anti-inflammatory effects.
Keywords: fish mucus; inflammation; carrageenan; rat paw edema; QH301-705.5; Arctic medicine. Tropical medicine; RC955-962; Biology (General); 14. Life underwater; 3. Good health